KEDUDUKAN LEMBAGA NEGARA DALAM MAKAN BERGIZI GRATIS - Denok Oktawila; Himawan Estu Bagijo; Tanudjaja Tanudjaja (Jurnal Media Informatika, 2025)
The free nutritious meal program is a plan to provide nutritious meals in schools or Islamic boarding schools to improve students' nutrition. Estimated number of beneficiaries (nationally) of the free nutritious meal program for 514 districts/cities with a total of 16,110,000 million school children. The aim of this research is to determine the application of Pancasila values through the free nutritious meal program. This research uses the Systematic Literature Review (SLR) method by identifying, reviewing, evaluating, and interpreting available research to be used as a data source. The aim of the free nutritious meal program launched by the government is closely related to the fifth principle of Pancasila, namely "Social Justice for All Indonesian People." Through this program, the government seeks to provide equal access to all students in Indonesia regardless of economic or social background. This program reflects the value of social justice because every individual is treated equally and gets the same benefits for the common good. This program is also expected to play a role in reducing social disparities. By providing free nutritious food, students from underprivileged families can have their nutritional needs met without having to be burdened with additional costs. Adequate dietary needs will help improve students' health and improve their learning abilities.